Nurses' Intent to Leave their Position and the Profession During the COVID-19 Pandemic. (October 2021) - Raso, Rosanne; Fitzpatrick, Joyce J.; Masick, Kevin
Abstract : OBJECTIVE: The aim of this study was to describe the relationships between perceptions of the pandemic impact on clinical nurses' and nurse leaders' intent to leave their current position and the profession and the differences in pandemic impact and intent to leave variables based on background factors. BACKGROUND: There is much discussion and concern about the COVID-19 pandemic impact on nurses' health and the nursing workforce. METHODS: More than 5000 nurses from a national sample participated in a cross-sectional, descriptive study. Participants rated their perceptions of the pandemic impact on their practice and their intent to leave their position and profession. RESULTS: Pandemic impact was rated high overall and was highest in nurses with 25+ years of experience and in managers/directors. Eleven percent of the total sample indicated they intended to leave their position, and 20% were undecided. Nurses who rated pandemic impact at the highest level had higher intent to leave their position. Of the respondents, less than 2% indicated they were leaving the nursing profession, whereas 8% were undecided. CONCLUSIONS: This is the 1st quantitative report of perceived level of pandemic impact on direct care nurses and nurse managers/directors at the time of this writing. The combination of those who intend to leave and those who are uncertain about leaving their positions could cause instability in the workforce if not reversed. Organizational attention to nurse well-being, work environment and staffing is imperative.